MicroRNA-92a Inhibits the Cell Viability and Metastasis of Prostate Cancer by Targeting SOX4. (14th September 2020) - Liao, Guolong; Xiong, Haiyun; Tang, Jiani; Li, Yamei; Liu, Ying
MicroRNAs (miRNAs) was confirmed to play an active role in the pathogenesis of prostate cancer (PCa). The expression and biological function for miR-92a in PCa remains unknown. In this study, we demonstrated that miR-92a expression was decreased in PCa tissues and cells lines. Overexpression miR-92a inhibited the cell viability, migration and invasion of PC-3 while inhibition of miR-92a led to opposite alteration of cell viability and metastasis of DU-145 cells. Mechanically, we confirmed that miR-92a interacted with 3'-UTR of SOX4 through the complementary sequences by luciferase reporter assay. qRT-PCR and western blot confirmed that miR-92a inhibited the expression of SOX4 in PCa cells. Moreover, overexpression of SOX4 reversed the inhibitory effects of miR-92a overexpression on PC-3 cell viability, migration and invasion, while knockdown of SOX4 suppressed the promoting effects of miR-92a knockdown on these biological functions of DU-145 cells. Therefore, our study indicates that miR-92a inhibits the growth and metastasis of prostate cancer by targeting SOX4, and can potentially serve as a biomarker and treatment target for PCa patients.